Estimated cost for cardiovascular disease risk-based management at a primary healthcare center in Nepal - Anu Aryal; David Citrin; Scott Halliday; Anirudh Kumar; Prajwol Nepal; Archana Shrestha; Rachel Nugent; Dan Schwarz (BMC, 2020)
Abstract Background Low- and middle-income countries are facing an increasing burden of disability and death due to cardiovascular diseases. Policy makers and healthcare providers alike need resource estimation tools to improve healthcare delivery and to strengthen healthcare systems to address this burden. We estimated the direct medical costs of primary prevention, screening, and management for cardiovascular diseases in a primary healthcare center in Nepal based on the Global Hearts evidence based treatment protocols for risk-based management. Methods We adapted the World Health Organization's non-communicable disease costing tool and built a model to predict the annual cost of primary CVD prevention, screening, and management at a primary healthcare center level. We used a one-year time horizon and estimated the cost from the Nepal government's perspective. We used Nepal health insurance board's price for medicines and laboratory tests, and used Nepal government's salary for human resource cost. With the model, we estimated annual incremental cost per case, cost for the entire population, and cost per capita. We also estimated the amount of medicines for one-year, annual number of laboratory tests, and the monthly incremental work load of physicians and nurses who deliver these services. Results For a primary healthcare center with a catchment population of 10,000, the estimated cost to screen and treat 50% of eligible patients is USD21.53 per case and averages USD1.86 per capita across the catchment population. The cost of screening and risk profiling only was estimated to be USD2.49 per case. At same coverage level, we estimated that an average physician's workload will increase annually by 190 h and by 111 h for nurses, i.e., additional 28.5 workdays for physicians and 16.7 workdays for nurses. The total annual cost could amount up to USD18,621 for such a primary healthcare center. Conclusion This is a novel study for a PHC-based, primary CVD risk-based management program in Nepal, which can provide insights for programmatic and policy planners at the Nepalese municipal, provincial and central levels in implementing the WHO Global Hearts Initiative. The costing model can serve as a tool for financial resource planning for primary prevention, screening, and management for cardiovascular diseases in other low- and middle-income country settings globally.